Strategy under ambiguity, and a new type of decision dilemma - Richard J. Arend (Administrative Sciences, 2022)
In this exploratory study, we challenge real decision makers to make choices in strategic games involving ambiguity, and to rationalize those choices. Such games are unique because they are not optimizable; however, the challenge such decisions represent-making choices over irreversible resource commitments in a competitive context and without complete information-is only growing in frequency in our modern business context. As such, our goal is to improve our understanding of real strategic decision making facing irreducible uncertainty, and then to identify ways to improve the outcomes. The challenge is that there are no theoretical solutions for these problems. (While such work has offered solutions, those have always involved watered-down problems-in terms of a lack of true uncertainty or a lack of true optimization). Thus, we approach the challenge from an experimental methodology as one alternative path toward improving outcomes. We do so by considering the influence of decision and decision-maker characteristics on the behaviors displayed while confronting these problems, with an eye on identifying vulnerabilities. We find that such characteristics correlate with expected behaviors, and that there exists potential room for improvements in the observed strategizing. The results of our study on the behaviors witnessed across three variants of our prototypical game-that represent increasing levels of complexity in the underlying ambiguity-have implications for theory and for practice, where one such conceptual implication involves the discovery of an entirely new form of the decision dilemma.
Keywords: 350; ambiguity; strategy; decision making; implied game; human subject experiment